Westonci.ca is the premier destination for reliable answers to your questions, brought to you by a community of experts. Explore a wealth of knowledge from professionals across various disciplines on our comprehensive Q&A platform. Join our platform to connect with experts ready to provide precise answers to your questions in different areas.
Sagot :
To solve the integral
[tex]\[ \int_2^3 \frac{x}{\sqrt{169-x^2}} \, dx, \][/tex]
we can follow these steps:
1. Identify the integrand: The integrand is [tex]\(\frac{x}{\sqrt{169 - x^2}}\)[/tex]. It suggests that a trigonometric substitution could be useful, or we might recognize a pattern of a derivative of an inverse trigonometric function.
2. Consider trigonometric substitution: Here, we recognize that [tex]\(169\)[/tex] is [tex]\(13^2\)[/tex], so we can use the substitution [tex]\( x = 13 \sin \theta \)[/tex], which implies that [tex]\(dx = 13 \cos \theta \, d\theta\)[/tex]. Also, [tex]\(13^2 - x^2 = 169 - 169 \sin^2 \theta = 169 \cos^2 \theta \)[/tex]. Hence, [tex]\( \sqrt{169 - x^2} = 13 \cos \theta \)[/tex].
3. Apply the substitution: Substitute [tex]\(x = 13 \sin \theta \)[/tex] and [tex]\(dx = 13 \cos \theta \, d\theta\)[/tex] into the integral.
[tex]\[ \int_2^3 \frac{x}{\sqrt{169-x^2}} \, dx = \int_2^3 \frac{13 \sin \theta}{13 \cos \theta} \cdot 13 \cos \theta \, d\theta = \int_2^3 \sin \theta \cdot 13 \, d\theta \][/tex]
4. Adjust the limits of integration: When [tex]\(x = 2\)[/tex], [tex]\(2 = 13 \sin \theta\)[/tex] thus [tex]\(\sin \theta = \frac{2}{13}\)[/tex], and when [tex]\(x = 3\)[/tex], [tex]\(3 = 13 \sin \theta\)[/tex] thus [tex]\(\sin \theta = \frac{3}{13}\)[/tex].
5. Evaluate the new integral: The integral in terms of [tex]\(\theta\)[/tex] is:
[tex]\[ \int_{\arcsin(\frac{2}{13})}^{\arcsin(\frac{3}{13})} 13 \sin \theta \, d\theta \][/tex]
6. Solve the integral: Using simple antiderivatives for the basic trigonometric function:
[tex]\[ \int 13 \sin \theta \, d\theta = -13 \cos \theta \][/tex]
7. Substitute back and evaluate at the bounds:
[tex]\[ \left[ -13 \cos \theta \right]_{\arcsin(\frac{2}{13})}^{\arcsin(\frac{3}{13})} \][/tex]
8. Calculate the cosine values of the bounds:
[tex]\[ -13 \cos(\arcsin(\frac{3}{13})) - (-13 \cos(\arcsin(\frac{2}{13}))) \][/tex]
9. Simplify using the relationships [tex]\( \cos(\theta) = \sqrt{1 - \sin^2(\theta)} \)[/tex]:
For [tex]\(\theta = \arcsin(\frac{2}{13})\)[/tex]:
[tex]\[ \cos(\arcsin(\frac{2}{13})) = \sqrt{1 - \left(\frac{2}{13}\right)^2} = \sqrt{\frac{169 - 4}{169}} = \sqrt{\frac{165}{169}} = \frac{\sqrt{165}}{13} \][/tex]
For [tex]\(\theta = \arcsin(\frac{3}{13})\)[/tex]:
[tex]\[ \cos(\arcsin(\frac{3}{13})) = \sqrt{1 - \left(\frac{3}{13}\right)^2} = \sqrt{\frac{169 - 9}{169}} = \sqrt{\frac{160}{169}} = \frac{\sqrt{160}}{13} \][/tex]
10. Substitute these values in:
[tex]\[ -13 \cdot \frac{\sqrt{160}}{13} - \left( -13 \cdot \frac{\sqrt{165}}{13} \right) \][/tex]
11. Combine and simplify:
[tex]\[ -\sqrt{160} + \sqrt{165} \][/tex]
Therefore, the value of the integral is:
[tex]\[ \boxed{-4\sqrt{10} + \sqrt{165}} \][/tex]
[tex]\[ \int_2^3 \frac{x}{\sqrt{169-x^2}} \, dx, \][/tex]
we can follow these steps:
1. Identify the integrand: The integrand is [tex]\(\frac{x}{\sqrt{169 - x^2}}\)[/tex]. It suggests that a trigonometric substitution could be useful, or we might recognize a pattern of a derivative of an inverse trigonometric function.
2. Consider trigonometric substitution: Here, we recognize that [tex]\(169\)[/tex] is [tex]\(13^2\)[/tex], so we can use the substitution [tex]\( x = 13 \sin \theta \)[/tex], which implies that [tex]\(dx = 13 \cos \theta \, d\theta\)[/tex]. Also, [tex]\(13^2 - x^2 = 169 - 169 \sin^2 \theta = 169 \cos^2 \theta \)[/tex]. Hence, [tex]\( \sqrt{169 - x^2} = 13 \cos \theta \)[/tex].
3. Apply the substitution: Substitute [tex]\(x = 13 \sin \theta \)[/tex] and [tex]\(dx = 13 \cos \theta \, d\theta\)[/tex] into the integral.
[tex]\[ \int_2^3 \frac{x}{\sqrt{169-x^2}} \, dx = \int_2^3 \frac{13 \sin \theta}{13 \cos \theta} \cdot 13 \cos \theta \, d\theta = \int_2^3 \sin \theta \cdot 13 \, d\theta \][/tex]
4. Adjust the limits of integration: When [tex]\(x = 2\)[/tex], [tex]\(2 = 13 \sin \theta\)[/tex] thus [tex]\(\sin \theta = \frac{2}{13}\)[/tex], and when [tex]\(x = 3\)[/tex], [tex]\(3 = 13 \sin \theta\)[/tex] thus [tex]\(\sin \theta = \frac{3}{13}\)[/tex].
5. Evaluate the new integral: The integral in terms of [tex]\(\theta\)[/tex] is:
[tex]\[ \int_{\arcsin(\frac{2}{13})}^{\arcsin(\frac{3}{13})} 13 \sin \theta \, d\theta \][/tex]
6. Solve the integral: Using simple antiderivatives for the basic trigonometric function:
[tex]\[ \int 13 \sin \theta \, d\theta = -13 \cos \theta \][/tex]
7. Substitute back and evaluate at the bounds:
[tex]\[ \left[ -13 \cos \theta \right]_{\arcsin(\frac{2}{13})}^{\arcsin(\frac{3}{13})} \][/tex]
8. Calculate the cosine values of the bounds:
[tex]\[ -13 \cos(\arcsin(\frac{3}{13})) - (-13 \cos(\arcsin(\frac{2}{13}))) \][/tex]
9. Simplify using the relationships [tex]\( \cos(\theta) = \sqrt{1 - \sin^2(\theta)} \)[/tex]:
For [tex]\(\theta = \arcsin(\frac{2}{13})\)[/tex]:
[tex]\[ \cos(\arcsin(\frac{2}{13})) = \sqrt{1 - \left(\frac{2}{13}\right)^2} = \sqrt{\frac{169 - 4}{169}} = \sqrt{\frac{165}{169}} = \frac{\sqrt{165}}{13} \][/tex]
For [tex]\(\theta = \arcsin(\frac{3}{13})\)[/tex]:
[tex]\[ \cos(\arcsin(\frac{3}{13})) = \sqrt{1 - \left(\frac{3}{13}\right)^2} = \sqrt{\frac{169 - 9}{169}} = \sqrt{\frac{160}{169}} = \frac{\sqrt{160}}{13} \][/tex]
10. Substitute these values in:
[tex]\[ -13 \cdot \frac{\sqrt{160}}{13} - \left( -13 \cdot \frac{\sqrt{165}}{13} \right) \][/tex]
11. Combine and simplify:
[tex]\[ -\sqrt{160} + \sqrt{165} \][/tex]
Therefore, the value of the integral is:
[tex]\[ \boxed{-4\sqrt{10} + \sqrt{165}} \][/tex]
Thank you for your visit. We are dedicated to helping you find the information you need, whenever you need it. Thanks for using our platform. We aim to provide accurate and up-to-date answers to all your queries. Come back soon. Thank you for using Westonci.ca. Come back for more in-depth answers to all your queries.